The Variable Rate Intravenous Insulin Infusion Protocol. Issue 2 (10th December 2013) - Collard, Benjamin; Sturgeon, Jonathan; Patel, Natasha; Asharia, Shabbar
Abstract: Insulin use among inpatients is high and associated with severe and regular medication errors. An initial baseline audit showed a wide variation in the prescription of intravenous insulin within the trust. These included variation in the choice of fluid prescribed, electrolyte levels not consistently checked, handwritten illegible prescriptions, and varying parameters set for adjustment of the prescription. A Variable Rate Intravenous Insulin Infusion protocol (VRIII)) was introduced to standardize intravenous insulin prescription throughout the trust by all members of the clinical team. We looked at and measured uptake and effects of the VRIII protocol in improving standardization of insulin prescription for inpatients on insulin at St George's NHS trust. The protocol was uploaded to the intranet to allow access 24 hours a day and the staff educated about it. The VRIII protocol was routinely used successfully throughout the trust. Any initial problems were addressed through education of clinical staff. The protocol has shown decreased prescribing and administrative errors, whilst demonstrating good glucose and electrolyte control. Use of a standardized protocol helps reduce medication errors and demonstrates good glycaemic control. Regular and continued education of clinical staff is necessary to maintain its efficacy.